2009
DOI: 10.1016/j.jep.2009.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NO in the inhibitory effect of Calotropis procera latex protein fractions on leukocyte rolling, adhesion and infiltration in rat peritonitis model

Abstract: Our study shows that LP fraction of Calotropis procera comprises of three distinct sets of proteins exhibiting anti-inflammatory and anti-nociceptive properties of which LP(PI) was most potent in inhibiting neutrophil functions and its effects are mediated through NO production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…The laticifer fluid of C. procera encompasses a large amount of proteins with anti-inflammatory properties and prospective pharmacological uses [11,18]. We have shown that the enhanced protection by LP or LP PI inoculums against Salmonella infection was not related to protease activity.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The laticifer fluid of C. procera encompasses a large amount of proteins with anti-inflammatory properties and prospective pharmacological uses [11,18]. We have shown that the enhanced protection by LP or LP PI inoculums against Salmonella infection was not related to protease activity.…”
Section: Discussionmentioning
confidence: 91%
“…The fractions corresponding to these peaks were dialyzed against distilled water and lyophilized. In the present study, LP PI was used because previous data have shown that this fraction is highly antiinflammatory [18].…”
Section: Procera Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory response associated with sepsis is well known to promote coagulation, and under these conditions, owing to the anti-inflammatory property of LP present in its subfraction LP PI , it produced a marked increase in the coagulation time as compared to septic control (Ramos et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Soluble proteins (latex proteins, LP) were recovered from the whole latex according to the method described by Lima-Filho et al (2010). LP was further fractionated by ion-exchange chromatography on a CM-Sepharose fast flow column to obtain three subfractions named LP PI , LP PII , and LP PIII according to Ramos et al (2009).…”
Section: Latex Protein Isolation and Ion-exchange Chromatographymentioning
confidence: 99%